2014
DOI: 10.9734/bjesbs/2014/5514
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Decision-making: A Study on Reflexive Relationship Between Leadership Style and Decision-making Approach

Abstract: Aims: This paper introduces how substantial decision-making and leadership styles relates with each other. Decision-making styles are connected with leadership practices and institutional arrangements. Study Design: Qualitative research approach was adopted in this study. A semi structure interview was use to elicit data from the participants on both leadership styles and decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The management of the COVID‐ 19 crisis means overcoming this crisis and the resulting crises by other scientific and administrative tools, avoiding its negatives and benefiting from its positives, to achieve balance and adapting to the various local and global variables and examining their effects and consequences in all fields. These findings agreed with the results of Kayode, Mojeed, and Fatai (2014) indicated that participatory decision‐makers style and consultative decision are the most favorite. As well as, Miller and Monge (1988) emphasized the participation in the decision‐making process.…”
Section: Resultssupporting
confidence: 91%
“…The management of the COVID‐ 19 crisis means overcoming this crisis and the resulting crises by other scientific and administrative tools, avoiding its negatives and benefiting from its positives, to achieve balance and adapting to the various local and global variables and examining their effects and consequences in all fields. These findings agreed with the results of Kayode, Mojeed, and Fatai (2014) indicated that participatory decision‐makers style and consultative decision are the most favorite. As well as, Miller and Monge (1988) emphasized the participation in the decision‐making process.…”
Section: Resultssupporting
confidence: 91%
“…The analysis used a qualitative research design where leaders from the Institute of Education International Islamic University Malaysia in 2012-2013 were used to gather data from participants on both leadership styles and decision-making in a semi-structured interview. The study's results indicate that, while leadership and decision-making styles are opaque in theory, they are closely related in reality (Kayode-Mojeed-Fatai, 2014).…”
Section: The Impact Of Artificial Intelligence On Decision Makingmentioning
confidence: 83%
“…The THOR project of Kejriwal (2019) as well the research papers by Kayode, Mojeed and Fatai (2014), Rabova, Konecny and Matiasova (2005) and Duan, Edwards and Dwivedi (2019) support the hypothesis -A.I. can have a big impact on leadership regarding the decision making process.…”
Section: The Impact Of Artificial Intelligence On Decision Makingmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it is also stated in the literature that leaders with strong leadership skills should have certain characteristics, such as vision, and that leaders focus on guiding employees with an innovation that is in line with the vision of the organization. It is also emphasized the importance of a leader being competent to make decisions by balancing many variables at the same time [12,13]. Based on this theoretical background, the basic leadership characteristics are determined as encouraging, guiding/coaching, effective communication, being innovative/creative, creating mission/vision, problem-solving, and decision-making in this paper.…”
Section: Introductionmentioning
confidence: 99%